2015
DOI: 10.15277/bjdvd.2015.042
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of calcaneal osteomyelitis: an unusual and severe form of diabetic foot disease

Abstract: Background: Osteomyelitis of the calcaneus is an uncommon type of diabetic foot infection considered to have a poor outcome. Little is known about predisposing and prognostic factors, or optimum treatment regimens. Conclusions: In patients with diabetes and heel ulcers, calcaneal osteomyelitis is associated with male gender, neuropathy and large deep ulcers. It is uncommon and has a poor prognosis. We were unable to identify any factors associated with improved prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this study, five patients with calcaneal osteomyelitis had delayed healing time in this study (141.20 ± 19.12 vs 124.69 ± 14.42). Paisley et al have reported a 33% healing rate at 30 weeks in diabetic heel ulceration with calcaneal osteomyelitis in comparison to 94% in those without osteomyelitis 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, five patients with calcaneal osteomyelitis had delayed healing time in this study (141.20 ± 19.12 vs 124.69 ± 14.42). Paisley et al have reported a 33% healing rate at 30 weeks in diabetic heel ulceration with calcaneal osteomyelitis in comparison to 94% in those without osteomyelitis 34 …”
Section: Discussionmentioning
confidence: 99%
“…Paisley et al have reported a 33% healing rate at 30 weeks in diabetic heel ulceration with calcaneal osteomyelitis in comparison to 94% in those without osteomyelitis. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Paisley et al have reported a 33% healing rate at 30 weeks in those with diabetic calcaneal osteomyelitis in comparison to 94% healing in those with heel ulceration without osteomyelitis. 14 Treatment usually demands resection of a key weight bearing area of the tuberosity within the proximity of Achilles tendon insertion. Earlier studies have reported varying healing rates from 35% to 74%.…”
Section: Introductionmentioning
confidence: 99%